Determination of the environmental risk index of the facilities of a federal multicampus institution of higher education - Senna, Ana Júlia Teixeira; Alves, Ricardo Ribeiro; Santos, Nara Rejane Zamberlan dos; Costa, Fabrício Lopes (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
The concern about sustainable development has been gaining momentum at public and private organizations, and they include Higher Education Institutions (HEI). For those organizations which have not yet adopted an Environmental Management System (SEM), a preliminary step consists in a survey and analysis of the environmental aspects and impacts. Therefore, the goal of this paper consisted in conducting a Survey of the Environmental Aspects and Impacts (SEAI) of a unit of a Federal Multicampus Institution of Higher Education, with the use of the Failures Modes and Effects Analysis (FMEA) tool, identifying the Environmental Risk Index (ERI). The choice of this method stemmed, basically, from the possibility to assess the environmental risks by virtue of the facility in implementing corrective actions, thus generating a list of actions to be developed in several time stages, allowing for beginning a SEM plan. After a collective visit to the venues, the environmental impacts and aspects of the following environments were verified on the spot: library / study hall; staff room / Educational Development Nucleus (EDN); recreation hall and corridors; restrooms; student administration services and laboratories. Through this survey it was possible to ascertain that the major potential cause of the environmental impacts is the poorly maintained electrical system.